Effects of COVID-19 in maternal and perinatal morbidity and mortality among obstetrics patients in tertiary care center - Hosna, Asma Ul; Jannat, Yeasmin Dil; Lipi, Munmun Nahar; Tamanna, Tabassum; Kadir, Syeed Mehbub Ul; Nipu, Ashraful Alam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: By the end of 2019, WHO had identified COVID-19 disease as a public health emergency. Research has focused on the impact of SARS-CoV-2 infection during pregnancy, including symptoms, disease severity, risk of vertical transmission, and perinatal and neonatal prognosis. Methods: This was a cross sectional prospective observational study, conducted at Gynae and Obstetric Department, in Bangabandhu Sheikh Mujib Medical University, between July 2020 to August 2021. 75 pregnant women who tested positive for COVID-19 were included in this study. Results: Most of the patients 29(38.7%) were aged 25-29 years. Majority 96% (72) of the cases were asymptomatic, symptomatic cases with cough were 4% (3). On the basis of our data, 94.7% (71) of the cases were Antenatal, while Postnatal and Abortion were 4% (3) and 1.3% (1) respectively. Complications such as fetal distress 25.3% (19), scar tenderness 17.3% (13), pre-eclampsia 12% (9), post-dated pregnancy 9.3% (7), previous 2LSCS with pain abdomen 2.7% (2), oligohydramnios 2.7% (2), malpresentation (transverse lie) 1.3% (1). All pregnant postpartum women were administered antibiotics and enoxaparin. 60% (45) were given HCQ, 40% (30) were given Antiviral drugs, 40% (30) were given Steroids. Injection methyl-prednisolone and tablet hydroxychloroquine 400 mg 12 hourly loading dose on day 1 followed by 200 mg 12 hourly for next 4 days and improvement in symptoms were noted. 16% (12) were managed conservatively and only 1.3% (1) were ICU admissions. Conclusions: In this study, we found that the majority of patients had moderate or no symptoms and discharged with satisfactory outcome.